2017
DOI: 10.1002/marc.201700710
|View full text |Cite
|
Sign up to set email alerts
|

4D Printed Actuators with Soft‐Robotic Functions

Abstract: troactive polymers, [7] as well as patterned hydrogels that shape-shift on swelling. [8,9] Further development of soft elements capable to perform complex motions or functions requires adequate materials and processing technologies that enable accurate control of the mechanical response. Moreover, on the route toward practical applications, there is often a necessity to have the possibility to miniaturize these elements, produce them in large dimensions or over large areas, or integrate them with other materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
322
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(331 citation statements)
references
References 27 publications
(62 reference statements)
9
322
0
Order By: Relevance
“…The locally different responsive properties of the hydrogels can be achieved by local adjusting the compositions and/or structures of the hydrogels. Among the reported methods, photolithographic 55,56 and three-dimensional (3D) printing methods [57][58][59][60][61] can produce hydrogels with macroscale inhomogeneous structures by introducing a double-network hydrogel or inducing different orientations of additive cellulose fibrils, respectively. Photolithographic, 62-66 electrochemical ionprinting, [67][68][69][70] ion-transfer-printing (ITP), 50 and ion-inkjetprinting (IIP) 71 methods can prepare hydrogels with molecular scale inhomogeneity by introducing crosslinking gradients into as-prepared hydrogels.…”
Section: Hydrogels With Locally Different Responsive Propertiesmentioning
confidence: 99%
“…The locally different responsive properties of the hydrogels can be achieved by local adjusting the compositions and/or structures of the hydrogels. Among the reported methods, photolithographic 55,56 and three-dimensional (3D) printing methods [57][58][59][60][61] can produce hydrogels with macroscale inhomogeneous structures by introducing a double-network hydrogel or inducing different orientations of additive cellulose fibrils, respectively. Photolithographic, 62-66 electrochemical ionprinting, [67][68][69][70] ion-transfer-printing (ITP), 50 and ion-inkjetprinting (IIP) 71 methods can prepare hydrogels with molecular scale inhomogeneity by introducing crosslinking gradients into as-prepared hydrogels.…”
Section: Hydrogels With Locally Different Responsive Propertiesmentioning
confidence: 99%
“…Additive manufacturing techniques, such as two‐photon lithography and 3D printing, are becoming more and more relevant in biotechnology, giving the possibility to produce complex 3D structures on different length‐scales and becoming amenable to many different materials . It has been shown that LC materials can be utilized with these techniques with the characteristic molecular order remaining preserved during the photo‐crosslinking process, or even induced and patterned due to shear forces in the 3D printing process . Van Oosten et al achieved the construction of bioinspired artificial cilia for mixing applications and microfluidic pumping (Figure d) .…”
Section: Polymeric Photoactuators: Moving Toward Artificial Musclesmentioning
confidence: 99%
“…López‐Valdeolivas et al prepared cross‐linkable liquid crystal polymers as inks and used them to print stimuli‐responsive structures. The printed elastomers were able to undergo shape changes in response to thermal stimulus and served as actuators or soft‐robots . Nishiguchi et al used a direct laser writing method to generate sophisticated and controlled folding of thermosensitive hydrogels.…”
Section: Applicationsmentioning
confidence: 99%
“…The printed elastomers were able to undergo shape changes in response to thermal stimulus and served as actuators or soft-robots. [97] Nishiguchi et al [98] used a direct laser writing method to generate sophisticated and controlled folding of thermosensitive hydrogels. The designed hydrogels were capable of biomimetic actuation.…”
Section: Bioactuators and Bioroboticsmentioning
confidence: 99%